Gender inequality in Canadian interuniversity sport: participation opportunities and leadership positions from 2010-11 to 2016-17. Issue 2 (3rd April 2021) - Norman, Mark; Donnelly, Peter; Kidd, Bruce
ABSTRACT: Combining results from four separate studies of gender equality in Canadian interuniversity sport, which were conducted biennially across four academic years (2010–11, 2012–13, 2014–15, and 2016–17), this paper analyses gender inequality in both athletic participation opportunities and leadership positions (coaching and administrative) across the 56 universities that comprise U SPORTS, the pan-Canadian governing body for Canadian interuniversity sport. Our findings indicate that Canadian interuniversity sport is characterised by persistent and ongoing gender inequality in both the opportunity to participate as an athlete and employment in leadership positions. We analyse these results in light of the historical struggle for women's opportunity in Canadian interuniversity sport and the development, but apparent lack of implementation, of U SPORTS' gender equity policies. We also critique the failure of U SPORTS and its member universities to act on the persistent gender inequality identified in our data, despite policy impetus to do so, and provide policy recommendations to address these inequalities.